A serious game to make learning Japanese (Katakana) easier - Siti Fairuz, Bahaman (2019)
Learning foreign language can be difficult at later age. Although, currently there are many different type of gaming apps and online material that can help people of all ages to learn foreign language. The problems are identified when user find it difficult to learn foreign language when the application is not engaging enough and user afraid of making mistakes when learning. Therefore, this project may solve those problems by designing and developing a serious game in order to increase learner’s ability to learn Japanese language and tests its system. There are two fields that needs to be considered in language learning and teaching using with video games. The two fields are Computer-assisted Language Learning (CALL) and Digital game-based Learning (DGBL). For this project, the fields that will be used is DGBL. It is not used as an assistance but to make the learning material more fun by adding few engaging game mechanics. This project uses Rapid Application Development methodology. In conclusion, this project has developed a useful game application that can be used by students and people interested in learning Japanese language.